Application of bitter wormwood in treatment of oncological diseases - Redka, A. M.; Baranovsky, M. M. (Problems of Environmental Biotechnology, 2019)
Purpose of the work was to describe antitumor activity of biologically active substances of bitter wormwood, the possibility of drug creating on its basis and bitter wormwood application in the complex treatment of oncological diseases. The influence of extractive substances of bitter wormwood on the M-NFS-60 and WISH cell lines was considered as well. The cell culture method based on cultivating of M-NFS-60 and WISH cell lines with an aqueous test extract of bitter wormwood in a 5 % CO2 atmosphere and live cells quantifying by fluorescence spectroscopy was considered in the article. It was found, that with an increase in the concentration of aqueous extract of bitter wormwood, cells M-NFS-60 and WISH die or lose their reproductive capacity. At 0,1 % concentration of aqueous extract the biologically active substances of bitter wormwood cause death of M-NFS-60 cells and loss of their reproductive capacity by 52,2 % (for number 1) and 52 % (for number 2); at 0,05% concentration by 44,7 % and by 47,4 %, respectively. With a decrease in the concentration of aqueous extract of bitter wormwood to 0,0016 %, cell survival is increasing and gradually reaching 100 %. At 0,1% concentration of aqueous extract of bitter wormwood it biologically active substances cause death of WISH cells and loss of their reproductive capacity by 78,6 % (for number 1) and 80,5 % (for number 2); at 0,05 % concentration – by 53,7 % and 60,3 % respectively. With a decrease in the concentration of aqueous extract of wormwood to 0,0016 %, cell survival is increasing and gradually reaching 100 %.